Moiré patterns in doubly differential electron-momentum distributions in atomic ionization by mid-infrared lasers - Dran, Martín Sebastián (2018)
We analyze the doubly differential electron momentum distribution in above-threshold ionization of atomic hydrogen by a linearly polarized mid-infrared laser pulse. We reproduce side rings in the momentum distribution with forward-backward symmetry previously observed by Lemell et al. [Phys. Rev. A 87, 013421 (2013)], whose origin, as far as we know, has not been explained so far. By developing a Fourier theory of moiré patterns, we demonstrate that such structures stem from the interplay between intra- and intercycle interference patterns which work as two separate grids in the two-dimensional momentum domain. We use a three-dimensional (3D) description based on the saddle-point approximation (SPA) to unravel the nature of these structures. When the periods of the two grids (intra- and intercycle) are similar, principal moiré patterns arise symmetrically as concentric rings in the forward and backward directions at high electron kinetic energy. Higher order moiré patterns are observed and characterized when the period of one grid is multiple of the other. We find a scale law for the position (in momentum space) of the center of the moiré rings in the tunneling regime. We verify the SPA predictions by comparison with time-dependent distorted-wave strong-field approximation calculations and the solutions of the full 3D time-dependent Schrödinger equation.